IoT-ATL: Prototype of a Digital Twin to Simulate Educational Scenarios in the Art and Technology Laboratories at the Departmental Institute of Fine Arts in Cali, Colombia - Ordóñez-Bolaños, Oswaldo-Andrés; Sierra-Martinez, Luz-Marina; Peluffo-Ordoñez, Diego-Hernán (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Digital Twins (DTs) have the potential to revolutionize the manufacturing, construction, maintenance, and control of industrial processes due to their ability to bridge the physical and digital realms. However, creating complex digital concepts requires carefully implementing appropriate methodologies and processes. This study presents a prototype digital twin of the art and technology laboratories at the Departmental Institute of Fine Arts in Cali, Colombia. We employ the Scrum agile development methodology to streamline the design and development process of the IoT-ATL prototype. A three-layer IoT architecture is established; it facilitates mapping the components of the digital twin and the physical elements to be simulated. The IoT-ATL prototype allows students and teachers to interact and learn about the physical state of the laboratory in a digital environment, thus increasing visibility of the availability and use of technological elements in the space.